2009
DOI: 10.1016/j.cell.2009.01.025
|View full text |Cite
|
Sign up to set email alerts
|

A PP2A Regulatory Subunit Regulates C. elegans Insulin/IGF-1 Signaling by Modulating AKT-1 Phosphorylation

Abstract: Summary The C. elegans insulin/IGF-1 signaling (IIS) cascade plays a central role in the regulation of lifespan, dauer diapause, metabolism and stress response. The major regulatory control of IIS is through phosphorylation of its components by serine/threonine-specific protein kinases. In a RNAi screen for serine/threonine protein phosphatases that counter-balance the effect of the kinases in the IIS pathway, we identified pptr-1, a B56 regulatory subunit of the PP2A holoenzyme. Modulation of pptr-1 affects p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
152
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 80 publications
4
152
0
Order By: Relevance
“…Consistent with these observations, a previous study reported that the activation of PI3K/AKT pathway was involved in suppression of MT expression in primary hepatocellular carcinoma (HCC) cells through inhibition of glycogen synthase kinase-3/C/EBP␣ signaling (56). PP2A B56␤ has been implicated in the dephosphorylation of AKT (57,58). Because glycogen synthase kinase-3 and C/EBP␣ are the downstream targets of PP2A, which plays a role in the regulation of cell growth and survival (59, 60), we thus speculate that PP2A B56␤ may affect MT expression via PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 73%
“…Consistent with these observations, a previous study reported that the activation of PI3K/AKT pathway was involved in suppression of MT expression in primary hepatocellular carcinoma (HCC) cells through inhibition of glycogen synthase kinase-3/C/EBP␣ signaling (56). PP2A B56␤ has been implicated in the dephosphorylation of AKT (57,58). Because glycogen synthase kinase-3 and C/EBP␣ are the downstream targets of PP2A, which plays a role in the regulation of cell growth and survival (59, 60), we thus speculate that PP2A B56␤ may affect MT expression via PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, it is plausible that Ppp2r2a is downstream of Akt and that another Pp2a regulatory subunit controls the subsequent downregulation of Akt. This is consistent with findings in Caenorhabditis elegans, in which B56β and not B55α (Ppp2r2a) is responsible for dephosphorylation of AKT-1 at the equivalent serine (Padmanabhan et al, 2009). RESEARCH ARTICLE Akt-dependent phosphatases and epidermal barrier Ppp2r2a knockdown leads to hyperphosphorylation of Jun, and Ppp2r2a and Jun bind in immunoprecipitation assays, providing evidence that Pp2a holoenzymes containing this regulatory subunit can directly target Jun, in agreement with reports that Pp2a interacts with Jun in bacterial two-hybrid assays (Avdi et al, 2002;Zhao et al, 2008).…”
Section: Research Articlesupporting
confidence: 80%
“…20 To investigate the phosphorylation state of AKT-1 we raised two mono-specific polyclonal antisera against different regions of AKT-1 (Supplementary Figure S2), immunoprecipitated endogenous protein from worm lysates and probed blots with phospho-specific antibodies to T350 (homologous to T308) and S517 (homologous to S473) previously generated. 22 In the absence of IR both T350 and S517 were phosphorylated, consistent with tonic insulin/IGF-1 signaling under normal growth conditions. Consistent with our genetic data suggesting noncanonical regulation of AKT-1, radiation did not dramatically alter the phosphorylation state of T350/ T308 in the wild-type compared to the unirradiated controls ( Figure 3a).…”
Section: Resultsmentioning
confidence: 89%